Report of a Father With Congenital Bilateral Absence of the Vas Deferens Fathering a Child With Beare–Stevenson Syndrome - Ferreira, Leonardo C.; Dantas Junior, José H. (Frontiers in Genetics, 2020)
Background Apert, Pfeiffer, and Crouzon syndromes are autosomal dominant diseases characterized by craniosynostosis. They are paternal age effect disorders. The association between paternal age and Beare–Stevenson syndrome (BSS), a very rare and severe craniosynostosis, is uncertain. Gain-of-function mutations in FGFR2 become progressively enriched in testes as men age and were shown to cause these syndromes. Case report Here, we describe a child affected with BSS, whose father was 36 years old and had congenital bilateral absence of the vas deferens (CBAVD). The child was heterozygous for the pathogenic FGFR2 variant c.1124A > G p.Tyr375Cys. By reviewing the literature, we found that BSS fathers are older than BSS mothers (mean age in years: 39 ± 10 vs 30 ± 6, p = 0.006). Male age greater than 34 years and CBAVD are both factors associated with poor spermogram parameters, which may represent an additional selective pressure to sperm carrying FGFR2 gain-of-function mutations. Conclusion These findings are consistent with the hypothesis that BSS is a paternal-origin genetic disorder. Further experimental studies would be needed to confirm this hypothesis.